Voices & Gestures: Comedy in Madrid during Francoism - Deltell Escolar, Luis; Fernández-Hoya, Gema (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
In this research we study the highest grossing Spanish films shot in the capital of Spain during the 1960s. We have selected four films. These plays are comedies. Madrid is important in these films. The corpus is: Atraco a las tres (José María Forqué, 1962); La ciudad no es para mí (Pedro Lazaga, 1966); Un millón en la basura (José María Forqué, 1966-1967) and No desearás al vecino del quinto (Tito Fernández, 1970).